Post-Divorce Matrimonial Property Distribution: A Case Study of Polygamy Marriage - Muhammad Kamran (CV. Social Politic Genius (SIGn), 2020)
This research aims to determine and understand what factors influence the effectiveness of post-divorce matrimonial property distribution in a case study of polygamy marriage in the Religious Court of Class 1A Makassar. This type of research is socio legal study research, and was conducted in Makassar City. The results showed that the effectiveness of post-divorce matrimonial property distribution in a case study of polygamy marriage in the Religious Courts of Class 1A Makassar can be seen based on five factors, including legal factors, law enforcement factors, facility factors, community factors, and cultural factors. Data obtained from all factors showed less effective results, including there, were 65% claims to legal factors, 72.5% claims to law enforcement factors, 60% claims to facility factors, 61.25% claims to community factors, and 62.5 % claims to cultural factors. Seriousness is needed, especially for law enforcement in carrying out their role, and it is hoped that all relevant stakeholders must socialize the rules regarding procedures for the post-divorce matrimonial property distribution.